Os dois lados da moeda: Técnica e projeto - Trujillo, Jorge Hernán Salazar (Risco - Journal of Architecture and Urbanism, 2006)
Consequences of the classical rupture between design workshops and other curriculum subjects, especially those contained in the Technical Area are analyzed from the optical of a teacher and a student, emphasizing on the problems related to the thematic separation of contents, characteristic of almost all Schools of Architecture. This discussion concludes with a statement that could help rebuild the academic focus in architecture as an integral discipline, as well as to settle some of the principal inconveniences detected.